Vimentin as a target for the treatment of COVID-19 - Zhenlin Li; Denise Paulin; Patrick Lacolley; Dario Coletti; Onnik Agbulut (BMJ Open Respiratory Research)
We and others propose vimentin as a possible cellular target for the treatment of COVID-19. This innovative idea is so recent that it requires further attention and debate. The significant role played by vimentin in virus-induced infection however is well established: (1) vimentin has been reported as a co-receptor and/or attachment site for SARS-CoV; (2) vimentin is involved in viral replication in cells; (3) vimentin plays a fundamental role in both the viral infection and the consequent explosive immune-inflammatory response and (4) a lower vimentin expression is associated with the inhibition of epithelial to mesenchymal transition and fibrosis. Moreover, the absence of vimentin in mice makes them resistant to lung injury. Since vimentin has a twofold role in the disease, not only being involved in the viral infection but also in the associated life-threatening lung inflammation, the use of vimentin-targeted drugs may offer a synergistic advantage as compared with other treatments not targeting vimentin. Consequently, we speculate here that drugs which decrease the expression of vimentin can be used for the treatment of patients with COVID-19 and advise that several Food and Drug Administration-approved drugs be immediately tested in clinical trials against SARS-CoV-2, thus broadening therapeutic options for this type of viral infection.